Sex estimation using the first lumbar vertebra by geometric morphometric analysis of 3D computed tomography in the Malaysian population. (September 2022) - Rohmani, Afiana; Shafee, Mohamed Swarhib; Ismail, Nik Azuan Nik; Hadi, Helmi; Nor, Faridah Mohd
Highlights: The first lumbar (L1) vertebra can be alternatively used for sex estimation. Using CT-scan images by GM technique, L1 vertebra was found to be sexually dimorphic. Coronal CT scan of the L1 vertebra played a crucial role in estimating sex. Vertebral body height was shown to be greater in females than males. Males displayed larger centroid size than females. Abstract: Sex estimation is vital in developing an accurate biological profile of human remains. The L1 vertebra have been reported to be sexually dimorphic by traditional metric method. Geometric morphometric (GM) is an advanced morphological analysis, which covers a mechanism to quantify size and shape characteristics. Objectives: This study analyzed the first lumbar vertebra (L1) from CT scan images by geometric morphometric for sex estimation in the Malaysian population. Materials and Methods: Samples were taken from 3D CT images of 226 adults, aged between 20 and 65 years old. A total of 27 landmarks were applied using Stratovan checkpoint software, and GM analysis was conducted by MorphoJ software. Results: There was a significant difference between sexes in centroid sizes of the L1 vertebra by independent t-test (p < 0.05). By Procrustes ANOVA, it showed significant difference in both shape and centroid size between sexes (p < 0.001). The principal component analysis (PCA) revealed vertebral body shape variation between different sexes. Discriminant function analysis (DFA) with cross-validation demonstrated 77.35% classification of sex, with accuracy rates of 74.7% for females and 80.0% for males. Conclusions: The L1 vertebral body is sexually dimorphic by 3D geometric morphometric among Malaysians. The sexual dimorphism does not relate to size dimorphism although males show larger centroid size than females. Graphical abstract: Image, graphical abstract